Benefits and pitfalls of virtual R&D teams: an empirical study - Ale Ebrahim, N.; Ahmed, S.; Taha , Z. (2010)
In this paper, advantages and drawbacks of virtual teams in research and development (R&D) are studied. With the globalization of commercial practices and advances in information and communication technologies, increasing numbers of enterprises are establishing cross-functional, geographically distributed virtual teams. Virtual teams in R&D are designed to access external resources and knowledge to maximize the competitive advantage from limited labor and resources. A survey has been conducted on 210 Malaysian and Iranian manufacturing companies, aimed to investigate the characteristics of R&D collaborations and extract the main advantages/disadvantages’ factors of virtual teams. These factors can be a guide line for R&D manager to achieve better performance of virtual teams.